1995
DOI: 10.2307/2983411
|View full text |Cite
|
Sign up to set email alerts
|

The Graphical Presentation of a Collection of Means

Abstract: SUMMARY When a study produces estimates for many units or categories a common problem is that end‐users will wish to make their own comparisons among a subset of these units. This problem will occur, for example, when estimates of school performance are produced for all schools. The paper proposes a procedure, based on the graphical presentation of confidence intervals, which enables such comparisons to be carried out while maintaining an average required type I error rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
357
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 470 publications
(381 citation statements)
references
References 1 publication
6
357
0
3
Order By: Relevance
“…However, note that the CrIs are appropriate only for comparisons against zero, but are too wide for comparison of any two hospitals. 62 Third, CrIs on the mobility dimension are wider than on any other dimension of the EQ-5D. This reflects the lesser amount of information contained in the data, with only two mobility categories being reasonably well populated.…”
Section: Risk-adjusted Hospital Performance On Individual Eq-5d Dimenmentioning
confidence: 98%
“…However, note that the CrIs are appropriate only for comparisons against zero, but are too wide for comparison of any two hospitals. 62 Third, CrIs on the mobility dimension are wider than on any other dimension of the EQ-5D. This reflects the lesser amount of information contained in the data, with only two mobility categories being reasonably well populated.…”
Section: Risk-adjusted Hospital Performance On Individual Eq-5d Dimenmentioning
confidence: 98%
“…Goldstein and Healy (1995) demonstrated that 95% CIs can overlap substantially and yet two means will be significantly different at the 5% level. They showed that if the standard errors of two independent means are approximately equal, then non-overlapping 84% CIs are equivalent to a t-test of these means at the .05 level (see also Tyron, 2001).…”
Section: Mean-level Changementioning
confidence: 99%
“…Till recently, there have been generally two traditional statistical procedures to deal with them: 1) the first procedure is to disaggregate all higher order variables to the individual level and carry out the analysis at individual level. Here, assumption of independence of observations cannot be ensured that is basic for the classical statistical techniques and hence can provide distorted results [1,2]; and 2) the second procedure is to aggregate the individual level variables to the higher level and do the analysis at higher level. Under this approach, all the within group information (variation) are thrown away which may be as much as 80% or 90% of the total variation before we start the analysis.…”
Section: Introductionmentioning
confidence: 99%